DEVELOPMENT AND RESEARCH OF A MULTI-POSITION HYDRO APPARATUS TECHNOLOGICAL MACHINE - KOROTYCH, OLНA; NEIMAK, VITALIY; ZOLOTENKO, ELLA; SUKHOSTAVSKIY, VADIM; MYKHAILOVSKY, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
According to the analysis of the designs of technological machines that have several executive mechanisms that work sequentially according to the technological diagrams and receive movements from the electric drive through chains of mechanical transmission mechanisms consisting of a set of kinematically connected friction pairs and parts, complicated in the design and its production, have reduced reliability in operation.The authors propose a developed hydraulic system for distributing motion to the working mechanisms of the technological machine, which consists of an original design of a multi-position, multi-line hydraulic apparatus, which can ensure the distribution of motion to several hydro motors of the working mechanisms of the technological machine in accordance with the cyclogram of its operation and replace the chains of mechanical transmission mechanisms and parts.The originality of the design of the multi-position, multi-line, single-spool hydraulic device is that it combines the properties of a spool- and valve-type hydraulic distributor, and the spool itself has a complex sectional cylindrical shape with cut sectors and makes a rotary, not reverse translational movement. The developed hydraulic device can perform both distribution and control functions and can replace controlled automatic devices.A math model for calculating the volume of the working cavities of the hydraulic device (hydraulic distributor) was developed.In order to check the operability of the hydraulic apparatus of the new design, its parametric modeling in the SolidWorks system and a cycle of experimental studies using the FloWorks module were carried out.The results of the distribution of liquid in the hydraulic apparatus for individual cavities connected to the hydraulic lines of the hydraulic motors of the working mechanisms of the technological machine were obtained.The principle of designing a new hydraulic device can be used to distribute liquid in technological machines with different cycles of mechanism interaction.
Keywords: hydraulic apparatus; cyclogram of work; hydraulic motors of executive mechanisms; mat model; numerical studies